Effectiveness of a Selective Partial Adductor Release for Chronic Adductor-Related Groin Pain in Professional Athletes. (March 2013) - Schilders, Ernest; Dimitrakopoulou, Alexandra; Cooke, Michael; Bismil, Quamar; Cooke, Carlton
Background: Chronic adductor enthesopathy is a well-known cause of groin pain in athletes. Currently, percutaneous nonselective adductor tenotomies give mixed results and not always predictable outcomes. Hypothesis: A selective partial adductor longus release as treatment for recalcitrant chronic adductor longus enthesopathy provides excellent pain relief with a prompt and consistent return to preinjury levels of sport. Study Design: Case series; Level of evidence, 4. Methods: All athletes were assessed in a standard way for adductor dysfunction. They received radiographs and a specifically designed magnetic resonance imaging groin study protocol. Only professional athletes who received a selective partial adductor release were included. Pain and functional improvement were assessed with the visual analog scale (VAS) pain score and time to return to sport. Results: Forty-three professional athletes (39 soccer and 4 rugby) with chronic adductor-related groin pain were treated with a selective partial adductor release. The average follow-up time was 40.2 months (range, 25-72 months). Forty-two of 43 athletes returned to their preinjury level of sport after an average of  9.21 weeks (range, 4-24 weeks; SD, 4.68 weeks). The preoperative VAS score improved significantly (Wilcoxon signed-rank test, P < .001) from 5.76 ± 1.08 (range, 3-8) to 0.23 ± 0.61 (range, 0-3) postoperatively. Conclusion: A selective partial adductor longus release provides excellent pain relief for chronic adductor enthesopathy in professional athletes with a consistent high rate of return to the preinjury level of sport.